What Drives Customer Satisfaction in Catering: Evidence from Palangka Raya - Aulia, Deanti; Hafizi, Muhammad Riza (AL-QARDH, 2022)
The catering business in Palangka Raya is increasingly competitive, so it demands that business people maximize business performance to be able to compete. This study aims to analyze product quality and service quality provided by Catering Aulia on customer satisfaction. Using a quantitative approach, this sample was taken by using the purposive sampling technique. In total, 92